"Hands-on" vs "arm's length" entrepreneurship research: Using ethnography to contextualize social innovation. Issue 3 (3rd January 2018) - Newth, Jamie
Abstract : Purpose: The purpose of this paper is to advocate for greater use of ethnographic research methods in entrepreneurship studies to produce more contextualized research. An argument for getting "up-close" and "hands-on" is presented to better understand how context shapes action in entrepreneurship than is presently achieved under the present entrepreneurship research orthodoxy. The need for contextualized research is particularly acute in the domain of social innovation. For its maturation as a field of research, it also requires stronger critical perspectives into the agendas and impacts of practitioners and other field-shaping actors. Ethnographic approaches are potentially powerful methods for revealing truths of this nature. Ethnographic methods are, however, problematic for professional researchers. The challenges of conducting such research are discussed. Design/methodology/approach: Conceptual paper regarding research methods in social innovation and social entrepreneurship studies. Findings: Social entrepreneurship that happens within established organizations is a hybrid social innovation activity that is informed, constrained, and compelled by idiosyncratic social contexts which are fashioned by institutional logics, identities, organizational culture, and history. With its contestable conceptualizations, priorities, models, purposes, and approaches, it arguably defies researchers' ability to build a deep understanding, from arm's length, of how the activity is undertaken for theory building purposes. Ethnographic methods enable deeper insight than traditional entrepreneurship research methods, and this research illustrates the differences between the espoused intentions, beliefs, and attitudes of managers and the lived experience of staff. Originality/value: Social entrepreneurship is a micro-level, hybrid social innovation activity that challenges embedded social, structural, and cultural norms when undertaken within established organizations. Ethnographic methods are under-utilized in exploring this and other forms of entrepreneurial action. This paper illustrates the value of ethnography for contextualizing social innovation research and that eschewing "arm's length" objectivity for "hands-on" insight is a powerful approach to empirically contextualizing social innovation and contributing to more critical perspectives and sophisticated theory building.